2017
DOI: 10.2147/dddt.s133172
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of novel <strong>EF24 </strong>and <strong>EF31 </strong>analogs as potential I&kappa;B kinase &beta; inhibitors for the treatment of pancreatic cancer

Abstract: Given the important role that inhibitory kappa B (IκB) kinase β (IKKβ) plays in pancreatic cancer (PC) development and progression, inhibitors targeting IKKβ are believed to be increasingly popular as novel anti-PC therapies. Two synthetic molecules, named EF24 and EF31, exhibited favorable potential in terms of inhibition of both IKKβ activity and PC cell proliferation. Aiming to enhance their cellular efficacy and to analyze their structure–activity relationship, four series of EF24 and EF31 analogs were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Later they optimized this formula as “lipidated Cur” which can achieve more than 5 μM in the brains of mice [ 106 , 107 ]. We have been working with this formula and found significant beneficial effects both in vivo and in vitro models of AD [ 108 ], and in an in vitro model of glioblastoma [ 14 ].…”
Section: Nano-technological Approaches For Cur Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Later they optimized this formula as “lipidated Cur” which can achieve more than 5 μM in the brains of mice [ 106 , 107 ]. We have been working with this formula and found significant beneficial effects both in vivo and in vitro models of AD [ 108 ], and in an in vitro model of glioblastoma [ 14 ].…”
Section: Nano-technological Approaches For Cur Deliverymentioning
confidence: 99%
“…Cur can inhibit the inflammatory cytokines, including IL1, IL6, TNF-α, IFN-γ, and COX-2 activity [ 152 ]. Several studies have demonstrated that Cur can inhibit activated astrocytes and microglia, as shown by reducing GFAP and Iba-1 levels [ 108 , 153 ] ( Figure 17 ). Therefore, as an anti-inflammatory natural polyphenol, Cur is a promising compound for tackling oxidative stress and inflammation in AD.…”
Section: Rationale For Cur Therapy In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al synthesized and purified 20 EF24 analogs, from which they identified one to have greater activity than EF24, showing potent anti-migration and anti-proliferative activity against A549 cells (89). Xie et al designed and synthesized four series of EF24 analogs, from which they found one displaying excellent inhibition of both IKKβ activity and pancreatic cancer (PC) development and progression (90). A group from Germany synthesized 14 EF24 analogs and revealed that they have promising anti-proliferative activity against eight cancer cell lines with low IC 50 values, and showed superior anti-angiogenic and vascular-disruptive effects (91).…”
Section: Biological Activities and Mechanisms Of Action Of Ef24mentioning
confidence: 99%
“…[16][17][18] Curcumin and its analogs EF24 and EF31 are also toxic, and there are huge defects in drug metabolism. [19][20][21] Therefore, finding a new type of IKKβ/NF-κB inhibitor with high efficiency and low toxicity, and exploring if it can reverse the resistance of gemcitabine has become our main research goal.…”
Section: Introductionmentioning
confidence: 99%